Energy and nutrient content of school lunches provided for children attending school-based nurseries: a cross-sectional study - Wall, Claire J; Pearce, Jo (Public health nutrition, 2023)
To nutritionally analyse lunches provided for 3-4-year-old children attending school nurseries. Energy and nutrient content are compared with nutrient frameworks underpinning voluntary guidelines for early years settings (EYS) and mandatory standards for infant schools (4-7-year-olds). A cross-sectional study, recording all main meals, vegetarian meals, jacket potato options, sandwich options and all desserts and accompaniments provided over 5 consecutive days in each school. Two portions of each meal were collected each day and weighed. Recipe and portion weight data were entered into nutrient analysis software. School nurseries where lunch was provided by the school. Nine schools, providing a total of 161 meals. Lunches contained more energy (1881 kJ/450 kcal), fat (15·5 g), free sugars (10·5 g) and Na (424 mg) than suggested by the nutrient framework for EYS. Carbohydrate (60·6 g), protein (16·8 g), fibre (6·7 g), Fe (2·4 mg), Zn (2·0 mg), Ca (202 mg), vitamin A (304 µg) and vitamin C (19 mg) also exceeded minimum recommendations. Compared with a revised nutrient framework for infant schools, energy was within range, whilst saturated fat, free sugars and Na were above maximum recommendations for this age group, and Zn was below. Sandwich meals were lower in vitamin C ( < 0·001- = 0·05) and Fe ( = 0·012- = 0·017) and higher in Na ( < 0·001- = 0·003) and Ca ( < 0·001- = 0·05). Lunches provided for children attending school nurseries are more in line with the framework for 4-7-year-olds. Free sugars, saturated fat and Na are areas of concern consistent with previous studies. Protein is three times more than recommended. Large portions of cakes and biscuits contribute to excess energy provision.